Multisegmental Diffuse Intradural Extramedullary Ependymoma: An Extremely Rare Case. Issue 2 (April 2014) - Guarnieri, Gianluigi; Tecame, Mario; Izzo, Roberto; Zeccolini, Fabio; Genovese, Luigi; Muto, Mario
Ependymoma has been described typically as an intramedullary tumour derived from ependymal cells with a predominance in women in the fifth decade of life. Pain is the most frequent symptom. Intradural extramedullary presentation is rarely described and almost always as a unique lesion. We describe a 53-year-old man with multi-segmental diffuse intradural extramedullary ependymoma with progressive lower leg hypoesthesia with regular motility. The patient's neurologic condition improved after surgery.